1019 Collaborative Surgical Team Training in Virtual Reality Is Superior to Individual Learning: A Randomised Controlled Trial. (19th August 2022) - Edwards, Thomas; Gupta, Shubham; Soussi, Daniella; Patel, Arjun; Khan, Sikandar; Liddle, Alexander; Cobb, Justin; Logishetty, Kartik
Abstract: Aim: This study aimed to assess if multiplayer virtual reality training was superior to single player training for acquisition of both technical and non-technical skills in learning complex open surgery. Method: 40 participants (20 novice surgeons and 20 novice scrub nurses) were enrolled in this study and randomised to solo or team virtual reality training learning anterior approach total hip arthroplasty. Solo participants trained with virtual avatar counterparts, whilst teams trained in pairs (surgeon and scrub nurse). Both groups underwent 5 VR training sessions over 6 weeks. Subsequently, they underwent a real-life assessment in which they performed AA-THA on a high-fidelity model with real equipment in a simulated operating theatre. Teams performed together and solo participants were randomly paired up with a solo player of the opposite role. Videos of the assessment were marked by two blinded expert assessors. The primary outcome was team performance as graded by the NOTECHs II score. Secondary outcomes were procedure time, technical errors from an expert pre-defined protocol and acetabular component positioning. Results: Teams outperformed solo trained participants in non-technical skills in the real-world assessment (NOTECHS-II score 50.3 ± 6.04 vs 43.90 ± 5.90, p=0.0275). They completed the assessment 28.11% faster than solos (31.22 minutes ±2.02 vs 43.43 ±2.71, p=0.01), and made close to half the number of technical errors when compared to the solo group (12.9 ± 8.3 vs 25.6 ± 6.1, p=0.001). Conclusions: Multiplayer training appears to lead to faster surgery with fewer technical errors and the development of superior non-technical skills.